The Role of Office Administration Education in the Digital Age - Delia Dhiva Pramesti; Kholid Kholid; Riesca Anindya Septantina (Journal of Managerial Sciences and Studies, 2024)
This article aims to provide knowledge and understanding about office administration training in today's digital age. Especially related to the capacity of managers in the field of office administration in the information age marked by digital technology. This study uses a deductive method. The method of discussion through observing the phenomenon of office administrative activities taking place in the field then involves theories and different perspectives expressed by experts in the field of administration and those who observe developments. technology development offered, as well as training for employees and office management games. Play an active role in every organization, because professional management of office administration will help organizational leaders have accurate, precise and timely data as a basis for decision making. The importance of the role of information in this digital age has led people to often refer to today's conditions as the information age. Deviating from that reality, each organization must position the office administration field accordingly.